Development of structural models of stability of investment projects in cyber security - Милов, Александр Владимирович; Евсеев, Сергей Петрович; Алексеев, Владимир Олегович (Ukrainian Scientific Journal of Information Security, 2018)
The need to study the behavior of an investment project for cybersecurity as a whole system and its resistance to synergistic threats is caused by the need to identify possible deviations in the process of its implementation and the need to influence them with the help of corrective actions to the cybersecurity system. It is shown that a variety of methods for studying sustainability is caused primarily by the presence of an ambiguous approach to the mathematical description of the cybersecurity system under study, the lack of a unified methodology for assessing the sustainability of investment projects for cybersecurity. This paper suggests an approach based on the application for studying the sustainability of an investment project for cybersecurity combining two types of description, namely, descriptions in the form of a transfer function and descriptions in the space of state variables of project. A model was proposed allows analyzing the sustainability of an investment project for cybersecurity using the study of the behavior of its transfer function using the method of drawing up typical structural schemes for constructing a model of investment projects for cybersecurity. To analyze the stability of investment projects of the closed type (with reinvestment), the Nyquist criterion based on the root locus method is used in the work. Obtained stability estimates for a conditional investment project of an open type and with reinvestment.